Human Brain Proteome - Neuhold, Lisa A. (International review of neurobiology, 2004)
Proteomics is a systematic approach for studying the identity and function of all proteins expressed in a cell, tissue or organ. New drug targets for diseases are often identified by comparing the proteome of the disease state to the normal state. As a result, proteomics has become increasingly important in the pharmaceutical and biotechnology industries as well as academics. This book contains five sections encompassing the research aspects of proteomics on the brain including the most recent advances in the technology and informatics. It discusses advances in high-throughput proteomic tech.